Recent Progress in Protein S-Nitrosylation in Phytohormone Signaling - Zhang, J.; Huang, D.; Wang, C.; Wang, B.; Fang, H.; Huo, J.; Liao, W.
The free radical nitric oxide (NO)is a critical regulator in modulation of wide range of growth and developmental processes as well as environmental responses in plants. In most cases, NO interacts with plant hormones to regulate these processes. It is clear that NO might work through either transcriptional or post-translational level. The redox-based post-translational modification S-nitrosylation has been recognized as a NO-dependent regulatory mechanism in recent years. In general, S-nitrosylation can be understood as a product of reversible reaction where NO moiety group covalently attaches to thiol of cysteine residue resulting in the formation of S-nitrosothiol in target proteins. Recently, the crosstalk between S-nitrosylation and phytohormones has been emerging. Furthermore, several proteins involved in plant hormone signaling have been reported to undergo S-nitrosylation, which might subsequently mediate plant growth and defense response. In this review, we focus on the recent processes in protein S-nitrosylation in phytohormone signaling. In addition, both importance and challenges of future work on protein S-nitrosylation in plant hormone network are also highlighted.